2021
DOI: 10.14309/crj.0000000000000531
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen-Driven Growth of Focal Nodular Hyperplasia: Truth or Myth?

Abstract: The etiologic association between focal nodular hyperplasia (FNH) and estrogen has been a subject of doubt and controversy. We present a case of a female patient with FNH that had been monitored for several years with noted size stability and later regression, who developed tumor growth during pregnancy. This case suggests that a subset of FNH is indeed hormone sensitive, as opposed to what has been frequently suggested by many other reports that question the association, a finding that may have clinical impli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…Kim and Ashbab reported that while FNH remains stable during pregnancy, tumor growth can still be detected in some patients, which increases the di culty of surgery and the risk of pregnancy [3,23,24]. This will increase the psychological burden of pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…Kim and Ashbab reported that while FNH remains stable during pregnancy, tumor growth can still be detected in some patients, which increases the di culty of surgery and the risk of pregnancy [3,23,24]. This will increase the psychological burden of pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…A few reports have shown that pregnancy and long-term use of oral contraceptives may lead to larger nodules in size and clinical manifestations, indicating a possible association between FNH and estrogen levels [ 62 , 63 , 64 , 65 ]. Indeed, a research team demonstrated that most FNH lesions showed estrogen receptor expression [ 66 ].…”
Section: Pathogenesis Molecular Features and Associated Diseasesmentioning
confidence: 99%
“…Focal nodular hyperplasia is the second most common benign liver tumor, occurring in 3% of adults 51 . The relationship between FNH and estrogen exposure is controversial, although tumor growth during pregnancy and subsequent regression postpartum has been reported 52 . Rare complications include intratumoral bleeding and rupture 52 .…”
Section: Liver Masses In Pregnancymentioning
confidence: 99%
“…The relationship between FNH and estrogen exposure is controversial, although tumor growth during pregnancy and subsequent regression postpartum has been reported 52 . Rare complications include intratumoral bleeding and rupture 52 . FNH is typically managed conservatively, although resection, embolization, or ablation can be considered in patients who are symptomatic 51,52 …”
Section: Liver Masses In Pregnancymentioning
confidence: 99%
See 1 more Smart Citation